ASSISTANCE IN E-FLYER CREATION TO SUPPORT PROMOTIONAL ACTIVITIES AT SECRET GARDEN VILLAGE BALI - Kirani, Luh Ketut Lovika Sesha; Kumara, I Nyoman Indra (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Secret Garden Village is a tourist destination that offers unique and diverse experiences with the concept of Edu-Vacation. In the increasingly competitive environment today, Secret Garden Village has yet to garner more attention on social media, particularly on Instagram. Upon reviewing previous content, Secret Garden's social media accounts have featured content that is overly luxurious or exclusive. This condition can pose a problem as it may create the perception that Secret Garden Village Bali is only intended for foreign tourists or financially capable segments of the market, thereby making local tourists less interested or feeling that the destination is not suitable for their budget or preferences. In an effort to increase revenue and business sustainability, it is important to attract more local tourists. Thus, creative e-flyer assistance is provided, tailored to the tastes and needs of the target market, as one of the promotional activities to introduce the tourist destination to the younger generation and local tourists and to increase public interest in the activities and facilities offered by Secret Garden Village.